Neoliberalism in your living room: A spatial cognitive reading of home design in IKEA catalogue. (October 2019) - Fawzy, Rania Magdi
Abstract: The paper examines the ways IKEA home design catalogue (2019) reflects and promotes the values of neoliberalism that underpin today's society. It seeks to relate the ideological and cognitive aspects of promoting home design to the verbalised materiality of the design as reflected in the catalogue. Doing so, the paper adopts a pragma-cognitive approach to trace the verbalised tempo-spatialities of IKEA design. The cognitive analysis is approached from a pragmatic lens, relying on the use of performatives and their lexicalized predicates (Condoravdi and Lauer's, 2011; Austin, 1962). The paper also synthesizes the Bakhtinian Chronotope (1981) with Multimodal Conceptual Metaphor (Forceville and Urios-Aparisi, 2009). Bakhtin's the chronotope is used to examine the inter-connectedness of temporal and spatial relationships depicted in IKEA catalogue to better understand the kinds of identities and values cognitively conveyed. Synthesizing Conceptual Metaphors with the chronotope is meant to define the paradigms of the spatial cognitive experience and materiality of IKEA home design while relating it to the logic of neoliberalism. Findings are in the connection between neoliberalism, both in its utopian and contradictory versions, and IKEA design options.